Chemi-mechanical pulping of durian rinds - Masrol, Shaiful Rizal; Ibrahim, Mohd Halim Irwan; Adnan, Sharmiza (Elsevier Science Ltd, 2015)
The physical, optical and mechanical characteristics of pulp and paper made from waste durian rinds as an alternative raw material for papermaking were investigated according to TAPPI and MS ISO standards. The durian rinds pulp was produced through chemi-mechanical pulping (CMP). Naturally dried durian rinds were treated with 10% Sodium Hydroxide (NaOH) based on oven dry (o.d) weight of durian rinds in room temperature for 2 hours and pulped by the refiner mechanical pulping (RMP) process. Experimental results show that durian rinds have great potential characteristics as newly explored non-wood based raw material for pulp and paper industry.